Desenvolvimento de uma rota tecnológica para obtenção de um produto funcional de yacon e suas implicações na saúde humana - Silva, Maria de Fátima Gomes da (2017)
The objective of this research was to define a technological route for an innovative and versatile product of yacon, rich in prebiotic fructooligosaccharides (FOS) and phenolic compounds, and as implications of functional product consumption in human health, through clinical trials. Initially, the Response Surface method was used to optimize the main process parameters of obtaining yacon clarified juice. For this, pectinolytic and cellulolytic enzymes, agitation and temperature were used as independent variables of the process, under 13 dependent responses (physic-chemical, chemical and permeate flux in the clarification by microfiltration). The results indicated that in the optimized conditions the permeate flux obtained was about 40% higher than the permeate flux of yacon pulp without enzymatic treatment, becoming a clear material with low turbidity (5.09 ± 0.08 NTU) and high levels of fructooligosaccharides (2.23 ± 0.47%; 2.33 ± 0.09%; 1.44 ± 0.11%, for GF2, GF3 and GF4, respectively) and chlorogenic acid (23.92 ± 2.03 μg g-1) were obtained. Subsequently, the clarified juice was used to obtain yacon syrup and its characterization was carried out by means of several analytical techniques, including NMR and UPLC-QToF-MSE. The syrup had a high concentration of FOS and CGA, in addition to presenting high levels of mineral elements, such as K, Ca and P. Essential amino acids such as valine, threonine and tryptophan were also observed. Among the 25 compounds tentatively identified, the main phenolic compounds derived from quinic and trans-cinnamic acids such as CGA, dicaffeoylquinic acid and esters of are highlighted. The influence of the different processing steps of yacon syrup on the phenolic profile, and on the composition of FOS and CGA was also evaluated. The results showed that there was no influence on the contents of FOS and CGA in the processing steps (pulp, enzymatic maceration and microfiltration), except for the last step (vacuum concentration), that these compounds presented a concentration about 6 times higher than the concentration found in yacon pulp. To evaluate the potential applications of yacon syrup in foods, a focal group was used. Among the observations made by the group, its application in yogurt stood out. Yogurt added yacon syrup showed hedonic values higher than 7.0 for global acceptance, appearance, aroma and flavor, corresponding to "liked very much" the "liked moderately", and 64% of the tasters indicated a positive attitude for the purchase of the product. To evaluate the effects of yacon syrup consumption on the satiety of healthy subjects, a visual analogue scale (VAS) test was used in short (1 day) and medium duration (15 days) trials. The results showed that there was treatment effect on "satiety" and "fullness" after stratification by sex, being statistically significant (P < 0.05) only for women after 15 days of consumption of yacon syrup. Finally, clinical trials were conducted to evaluate the impact of daily consumption (totaling 15 days) of yacon syrup on the glycemic, lipid and inflammatory metabolism of healthy individuals, as well as hormones related to satiety such as ghrelin and GLP- 1. The results did not reveal significant differences (P > 0.05) in the indices evaluated during the study, but a tendency - although not significant - was observed in the increase of the GLP-1 hormone during the period evaluated. In this way, the product obtained was differentiated from a nutritional and functional point of view, responding to a market niche avid for innovative products in the area of functional foods, and the technological process used was suitable for obtaining a high-quality product.